Leaving Spain : A Biographical Study of an Economic Crisis and New Beginnings - Riemann, Mê-Linh (Book collections on Project MUSE., 2022)
Since the beginning of the economic crisis of 2008, Spain, like other Southern European countries, has witnessed a mass departure of mostly young people looking for opportunities abroad. 'Leaving Spain' is based on 58 autobiographical narrative interviews with recent Spanish migrants who went to the UK and Germany, and sometimes returned. By presenting a combination of in-depth case studies and comparative analyses, the author demonstrates the potential of biographical research and narrative analysis in studying contemporary Europe, including its overlapping crises. The scope of the sociological study is not limited to examining how those who left Spain experienced single phases of their migration. Instead, it focuses on the significance of migration projects in the context of their life histories and how they make sense of these experiences in retrospect.0This book will not only be of great interest to social scientists and students in different disciplines and interdisciplinary studies such as sociology, anthropology, human geography, European studies, education, and social work, but also to professionals, European and national policy makers, and those interested in learning more about migrants? experiences, perspectives, and (often invisible) contributions.